Iron in the General Population and Specificities in Older Adults: Metabolism, Causes and Consequences of Decrease or Overload, and Biological Assessment - Manckoundia P (Dove Medical Press, 2020)
Patrick Manckoundia,1 Amadou Konaté,2 Arthur Hacquin,1 Valentine Nuss,1 Anca-Maria Mihai,1 Jérémie Vovelle,1 Mélanie Dipanda,1 Sophie Putot,1 Jérémy Barben,1 Alain Putot1 1“Pôle Personnes Âgées”, Hospital of Champmaillot, University Hospital of Dijon Burgundy, Dijon, France; 2Unit of Diagnosis and Rapid Orientation (DIAGORA), Internal Medicine Department, Hospital of Saint-Eloi, University Hospital of Montpellier, Montpellier, FranceCorrespondence: Patrick Manckoundia Service de Médecine Interne GériatrieHôpital de Champmaillot CHU, 2, Rue Jules Violle, Dijon Cedex 21079, FranceTel + 333 80 29 39 70Fax + 333 80 29 36 21Email patrick.manckoundia@chu-dijon.frAbstract: Iron is involved in many types of metabolism, including oxygen transport in hemoglobin. Iron deficiency (ID), ie a decrease in circulating iron, can have severe consequences. We provide an update on iron metabolism and ID, highlighting the particularities in older adults (OAs). There are three iron compartments in the human body: 1) the functional compartment, which consists of heme proteins including hemoglobin, myoglobin and respiratory enzymes; 2) iron reserves (IR), which consist mainly of liver stocks and are stored as ferritin; and 3) transferrin. There are two types of ID. Absolute ID is characterized by a decrease in IR. Its main pathophysiological mechanism is bleeding, which is often digestive and can be due to neoplasia, frequent in OAs. Biological assessment shows low serum ferritin and transferrin saturation (TS) levels. Furthermore, hypochromic microcytic anemia is frequent, and the serum-soluble transferrin receptor (sTfR) level is high. Functional ID, in which IR are high or normal, is due to inflammation, which is also frequent in OAs, particularly in its chronic form. Biological assessments show high serum ferritin, normal or low TS, and normal sTfR levels. Moreover, C-reactive protein is elevated, and there is moderate non-regenerative non-macrocytic anemia. The main characteristics of iron metabolism anomalies in the elderly are the high frequency of ID (20% of ID with anemia in adults ≥ 85 years) and the severity of its consequences, which include cognitive impairment in case of ID or iron overload and decrease of physical activity in case of ID. In conclusion, causes of ID are frequently intertwined in OAs as a result of the polymorbidity that characterizes them. ID can have dramatic consequences, especially in frail OAs. Thus, measuring the appropriate biological markers prevents errors in the positive diagnosis of ID type, clarifies etiology, and informs treatment-related decision-making.Keywords: anemia, iron deficiency, iron metabolism, older adults